Ethical aspects in the use of radiation in medicine: update from ICRP Task Group 109. (December 2020) - Bochud, F.; Cantone, M.C.; Applegate, K.; Coffey, M.; Damilakis, J.; del Rosario Perez, M.; Fahey, F.; Jesudasan, M.; Kurihara-Saio, C.; Le Guen, B.; Malone, J.; Murphy, M.; et al.
Whereas scientific evidence is the basis for recommendations and guidance on radiological protection, professional ethics is critically important and should always guide professional behaviour. The International Commission on Radiological Protection (ICRP) established Task Group 109 to advise medical professionals, patients, families, carers, the public, and authorities about the ethical aspects of radiological protection of patients in the diagnostic and therapeutic use of radiation in medicine. Occupational exposures and research-related exposures are not within the scope of this task group. Task Group 109 will produce a report that will be available to the different interested parties for consultation before publication. Presently, the report is at the stage of a working document that has benefitted from an international workshop organised on the topic by the World Health Organization. It presents the history of ethics in medicine in ICRP, and explains why this subject is important, and the benefits it can bring to the standard biomedical ethics. As risk is an essential part in decision-making and communication, a summary is included on what is known about the dose–effect relationship, with emphasis on the associated uncertainties. Once this theoretical framework has been presented, the report becomes resolutely more practical. First, it proposes an evaluation method to analyse specific situations from an ethical point of view. This method allows stakeholders to review a set of six ethical values and provides hints on how they could be balanced. Next, various situations (e.g. pregnancy, elderly, paediatric, end of life) are considered in two steps: first within a realistic, ethically challenging scenario on which the evaluation method is applied; and second within a more general context. Scenarios are presented and discussed with attention to specific patient circumstances, and on how and which reflections on ethical values can be of help in the decision-making process. Finally, two important related aspects are considered: how should we communicate with patients, family, and other stakeholders; and how should we incorporate ethics into the education and training of medical professionals?